A new approach to identify unilateral functional hearing loss - Vyasa Murthy MN (Journal of All India Institute of Speech and Hearing, 1971)
The main principle of disclosing unilateral functional hearing loss is to confuse the patient regarding which ear is being tested. This principle has been used in almost all tests of unilateral functional hearing loss including Stenger, Speech Stenger, Shifting voice and Switched Speech tests (Newby 1965, Jerger- 1963). Using the same principle but on different approach it is possible to disclose unilateral functional hearing loss. The new approach is to make use of 'Binaural summation'. Two methods have been described.